Orbital Myositis with Sudden Visual Loss: A Case Study in Niamey, Niger - Abba Kaka H.Y.; Guirou N.; Moussa M.; Boubacar M.; Amza A. (European Scientific Journal, ESJ, 2018)
This paper focuses on presenting a case study of three cases of orbital myositis in one male and two female adult patients. All patients presented sudden loss of vision and proptosis at the initial stage. Ophthalmological examination outlined optic nerve atrophie. The diagnosis of all cases was confirmed with a CT scan which showed specific muscle inflammation. The treatment was successfully carried out using bolus doses of corticosteroids relayed with oral prednisolone for over 6 weeks. Six (6) months follow-up, however, did not show any relapse in all the cases.